تأثير أبعاد التسويق عبر الهاتف المحمول على ولاء الزبون - قريبيز ،حسام الدين; ساحي ،مصطفى (جامعة الوادي University of Eloued, 2024)
This study aims to shed light on the impact of mobile marketing dimensions on customer loyalty among a sample of mobile marketing application users who rely on these applications for making purchasing decisions. The study focuses on a set of dimensions (interaction, personalization, location, and convenience). Data was collected using a questionnaire from a sample of 294 respondents and analyzed using SPSS V26 software. The study concluded that there is a statistically significant positive relationship between the dimensions of mobile marketing and enhancing customer loyalty among the study sample. The convenience dimension was found to have the most significant impact.
The Impact of Mobile Marketing Dimensions on Customer Loyalty: An Empirical Study on Mobile Marketing Application Users
Keywords: التسويق عبر الهاتف المحمول; ولاء الزبون; القرارات الشرائية; Mobile Marketing; Customer Loyalty; Purchasing Decisions.